Classical Greek philosophy - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2004)
This program featuring Princeton University's Alexander Nehamas and Richard Sorabji, honorary fellow at Wolfson College, the University of Oxford, addresses core topics in ancient philosophy such as freedom and fate, permanence and change, happiness, the nature of the cosmos, and the immortality of the soul. Concepts as articulated by key figures including Socrates, Plato, Aristotle, Heraclitus, Pythagoras, and the Milesian and Eleatic philosophers in combination with quotations drawn from Plato's Republic, Aristotle's Physics, and other influential sources
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD format
Keywords: Philosophy; Philosophy -- History; Philosophy, Ancient